Kajian elemen penilaian prestasi bangunan bagi menilai premis Institusi Pendidikan Tinggi Swasta (IPTS) ke arah menambah baik kualiti bangunan pendidkan tinggi / Noor Hasniza Mat Salleh - Noor Hasniza, Mat Salleh (2017)
The purpose of this study is to determine the appropriate building performance elements in assessing the performance of private higher education institution's (PHEI) building. Determination of performance elements was intended to improve current valuation tools used by MOHE to establish effective and comprehensive assessment methods. The study was divided into two phases. The first phase comprises of literature and needs analysis study that was conducted on 262 Chief Executive of PHEI. Literature review is carried out to identify the performance elements and its importance in influencing HEI's building quality based on industry player perspective. The data was analysed by descriptive statistics using the Statistical Package for the Social Science (SPSS) version 21.0 software. The interpretation of this requirement was based on the mean value and the result of two hypothesis tests that have been conducted. The findings have identified five main categories of performance with 10 main assessment criteria and 33 building performance elements that suits the study. In the second phase, expert consensus survey comprising 23 specialists in the field of study was conducted. At this stage, data was analysed by using the Fuzzy Delphi Method (FDM) approach to determine the appropiate performance element as the parameter of building performance assessments for PHEI. The results confirmed that only 30 performance elements were verified to assess the PHEI's building. Based on these results, the comparison of the performance elements in the building assessment tool has been made to guide the MOHE in improving the existing assessment tool towards better PHEI's building quality.